The Experts Are Not Enough - Hurlbut, J. Benjamin (The Hastings Center report, 2019)
As Achim Rosemann and colleagues rightly suggest in their article “Heritable Genome Editing in Global Context: National and International Policy Challenges,” in this issue of the Hastings Center Report, the scientific, ethical, and governance challenges associated with heritable genome editing are global in scope. Both the genetic interventions and the social and moral judgments about human identity and integrity associated with them will affect all humanity. Yet the worries, problems, and solutions that the study illuminates reflect only a partial picture of those challenges. That is to be expected from a study of this sort: the “stakeholders” who were consulted are a limited group and as such are bound to provide a particular, limited picture. One of the important contributions that such a study can make is in providing a picture of what problems particular kinds of experts see as the primary problems and how the framing of those problems may displace other questions and perspectives, especially when such parochial framings of problems are elevated to the level of the “global.” Rosemann et al. do not explain how participants were identified as stakeholders or, indeed, how the study identified the stakes. This is a missed opportunity, and it points toward a set of questions that themselves need to be asked about how the stakeholders—and the stakes—of global governance of heritable genome editing are identified.